Macrofungi Diversity in Mount Gede Pangrango National Park - Supratman, Lilis; Alfieansyah, Muhammad; Noviani, Sela; Raihana, Naura (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2024)
Macrofungi are easily observed biodiversity. Mount Gede Pangrango National Park is a complex research location for inventorying macroscopic macrofungi. The rainy season is a strategic time for abundant macrofungi research. The purpose of this study was to inventory macrofungi and their relationship to the role of macrofungi through literature studies. The method used in this study was the free roaming method with sampling using the purposive sampling technique. Observations were made when macrofungi were found on the path to the Cibeureum waterfall at an altitude of 1,625 m above sea level. Information about the role of macrofungi with comparative studies with literature. The results of the study of macrofungi identification was using the determination key on various applications of macrofungi. The result found 5 orders, 10 families, 15 genera and 19 species. The role of macroscopic fungi associated with macroscopic for consumption (Phillipsia, Laetiporus, and Lentinus), macroscopic herbal fungi (Microporus, Tatraea, Ganoderma, and Trametes), macroscopic pathogenic fungi (Phellinus), macroscopic wood-destroying fungi (Phellinus) and macroscopic bioluminescent fungi (Picipes and Mycena). It can be concluded that the most dominant order found is Polyporales, and the most dominant family is Polyperaceae. The role of macroscopic fungi in study site are for consumption, macroscopic herbal fungi, macroscopic pathogenic fungi, macroscopic wood-destroying fungi, and macroscopic bioluminescent fungi.